Determinants of Earnings Resilience: Can the Difference Between Book Value and Tax, Market Concentration, and Debt Level be Determined by Cash Flow? - Faolina, Faolina; Noorrochmawatie, Rizky; Sri Lastanti, Hexana (AKRUAL: Jurnal Akuntansi, 2025)
Research Background: The urgency of this research is increasingly relevant, considering the phenomenon of economic instability and global oil price volatility, which have a significant impact on the oil and gas sector in Indonesia. Introduction / Objectives: The purpose of this scientific study is to deeply explore the influence of Book Tax Difference, Market Concentration, and Debt Level on Earnings Persistence, with Cash Flow as a moderating variable in oil and gas sector companies listed on the Indonesia Stock Exchange. Methods: The method used is quantitative research with descriptive statistical analysis and SEM. The secondary data used comes from the financial statements of companies included in the study population, oil and gas companies, with a sample of 16 companies selected through census techniques. Results: The results indicate that BTD, Cash Flow, and Debt Level have a significant influence on Earnings Persistence, while Market Concentration has an effect that is close to significant. In terms of moderation, only Moderating Effect 2 shows almost significant results. Conclusion: The implications of this research provide insight for oil and gas companies and investors regarding the factors that influence profit sustainability and offer direction for more effective financial management, particularly in optimizing cash flow and debt structure to maintain profit stability.